SUPERVISION OF SCHOOL SUPERVISORS BASED ON SPIRITUAL APPROACH (An Initial Draft) - Jamaluddin Jamaluddin (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2022)
Madrasas are Islamic educational institutions that have a major role in developing Islamic education that is growing. This of course cannot be separated from the role of the government which regulates its governance, including by implementing supervision of its implementation as an effort to improve the quality of learning. School/madrasah supervisors have an important role in providing enlightenment and directing schools/madrasas so that they can run optimally. The purpose of this study is to design and develop a model for supervising school supervisors based on a spiritual approach so that the role of supervision is not only oriented to the right or wrong of a job but as a companion who can guide schools/madrasahs towards improvement in instructional based on a spiritual approach.In the data collection process, library research methods were used and data collection was taken from the theory of educational supervision and Islamic teaching sources in order to obtain a spiritual-based supervision model that could be implemented in the supervisory activities of school/madrasah supervisors. The draft that has been compiled is then discussed involving experts consisting of lecturers and school/madrasah supervisors who are distributed via google form. The results of this study indicate that the supervisory model of school/madrasah supervisors based on a spiritual approach consists of: 1) supervisory duties as a mandate from Allah swt, 2) supervisor duties as a charity, 3) supervisor duties as the obligations of knowledgeable and knowledgeable people, 4) supervisor duties as the recipient of the baton of the struggle of the Prophet Muhammad.